Pneumorrhachis in children: A report of two cases and review of the literature - Kazufumi Yaginuma, MD; Masahiro Watanabe, MD, PhD; Yasushi Saito, MD; Nobuhisa Takahashi, MD; Yoshihiro Ohara, MD, PhD; Shogo Kobayashi, MD, PhD; Kazuhiro Mochizuki, MD, PhD; Kazuhide Suyama, MD, PhD; Masatoki Sato, MD, PhD; Hideki Sano, MD, PhD; Koichi Hashimoto, MD, PhD; Atsushi Kikuta, MD, PhD; et al. (Radiology Case Reports, 2019)
Pneumorrhachis refers to the clinical presentation of air within the spinal canal, and it is rarely associated with pneumomediastinum, particularly in young children. Pneumorrhachis associated with pneumomediastinum is generally asymptomatic. Here we report 2 unusual cases involving very young children with pneumorrhachis secondary to pneumomediastinum and present a review of the relevant literature. Case 1 involved a 4-year-old girl who presented with wheezing, violent coughing, and dyspnea associated with bronchiolitis. Case 2 involved a 3-year-old boy who presented with wheezing, violent coughing, and dyspnea associated with interstitial pneumonia possibly caused by graft-versus-host disease with human herpesvirus 6 infection after allogeneic hematopoietic stem cell transplantation. In both cases, pneumorrhachis improved with oxygen inhalation therapy and treatment of the underlying disease. Pneumorrhachis is rarely associated with neurological problems; however, decompressive laminectomy may be indicated to relieve the air block. Because pneumorrhachis is rare in children and neurological sequelae may be difficult to identify, close clinical, and radiographic observations are necessary. Plain radiography is not sufficient, and computed tomography should be performed to rule out intraspinal air. Keywords: Pneumorrhachis, Pneumomediastinum, Children